2007
DOI: 10.1016/j.neulet.2007.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urinary odor-induced glomerular activation in the main olfactory bulb of aromatase knock-out and wild type female mice

Abstract: Previously [D.W. Wesson, M. Keller, Q. Douhard, M.J. Baum, J. Bakker, Enhanced urinary odor discrimination in female aromatase knockout mice, Horm. Behav. 49 (2006) [580][581][582][583][584][585][586] female aromatase knock out mice successfully learned to discriminate in a food-motivated go/no-go task between urinary volatiles from ovariectomized female mice treated with estradiol as opposed to estradiol plus progesterone whereas wild type females failed to learn this odor discrimination. We asked whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This result is surprising since previous studies showed statistically significant differences in the profiles of MOB glomerular activation following exposure to different urinary odor stimuli, such as urinary volatiles from ovariectomized females given estradiol alone versus those from ovariectomized females treated with estradiol plus progesterone (Martel et al, 2007), suggesting that urinary odors vary according to the hormonal status of the female. Likewise, Schaefer and co-workers (Schaefer et al, 2001; Schaefer et al, 2002) showed that distinct clusters of MOB glomeruli were activated in female mice exposed to urinary volatiles from males carrying different haplotypes of the major histocompatibility complex.…”
Section: Discussionmentioning
confidence: 61%
“…This result is surprising since previous studies showed statistically significant differences in the profiles of MOB glomerular activation following exposure to different urinary odor stimuli, such as urinary volatiles from ovariectomized females given estradiol alone versus those from ovariectomized females treated with estradiol plus progesterone (Martel et al, 2007), suggesting that urinary odors vary according to the hormonal status of the female. Likewise, Schaefer and co-workers (Schaefer et al, 2001; Schaefer et al, 2002) showed that distinct clusters of MOB glomeruli were activated in female mice exposed to urinary volatiles from males carrying different haplotypes of the major histocompatibility complex.…”
Section: Discussionmentioning
confidence: 61%
“…Fos was quantified at both the dorsal and ventral parts of the MOB as previous studies (Schaefer et al. , 2001; Martel et al. , 2007) have shown that volatile urinary odours preferentially activate the ventral MOB.…”
Section: Methodsmentioning
confidence: 76%
“…Both wild-type and ArKO females successfully learned to discriminate between other types of volatile urinary odors, including those from gonadally intact male versus ovariectomized females primed with estradiol + progesterone and those from gonadally intact versus castrated males. However, the different capacities of WT and ArKO females to discriminate volatile urinary odors from ovariectomized females treated with estradiol as opposed to oestradiol + progesterone cannot be explained by a difference between females of these two phenotypes in the ability of these two odors to activate distinguishable clusters of MOB glomeruli [70], suggesting that the central processing of social odors may be affected in female ArKO mice. In this respect, ArKO females that were treated with estradiol benzoate in adulthood to correct for their estrogen deficiency showed a normal, female-typical, Fos activation at the level of the olfactory bulbs when exposed to male urinary odors, but Fos responses were affected at more central levels [85].…”
Section: Sexual Differentiation Of Both Olfactory Systemsmentioning
confidence: 95%
“…without direct physical contact with the olfactory source) remains controversial but some experiments reported the activation of the AOB by volatile compounds delivered in the airstream [70,118]. In addition, other indirect behavioral evidence for a role of the VNO in the detection of volatile molecules comes from the study by Trinh and Storm [109], who used transgenic mice with a nonfunctional cAMP signaling pathway in the olfactory epithelium due to a mutation in type 3 adenylyl cyclase (AC3).…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%